2007
DOI: 10.1002/ppul.20736
|View full text |Cite
|
Sign up to set email alerts
|

A phase 2 study of aztreonam lysine for inhalation to treat patients with cystic fibrosis and Pseudomonas aeruginosa infection

Abstract: Summary. Background: Aztreonam lysine for inhalation (AZLI) is being developed for treatment of CF patients with Pseudomonas aeruginosa airway infection. Methods: This double-blind, randomized, placebo-controlled Phase 2 study evaluated the safety, tolerability and efficacy of 75 and 225 mg AZLI administered BID for 14 days using the eFlow 1 Electronic Nebulizer (Pari Innovative Manufacturers, Inc., Midlothian, VA). Patients were 13 years and older with FEV 1 ! 40% predicted, chronic P. aeruginosa infection, a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
62
1
2

Year Published

2010
2010
2022
2022

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 99 publications
(67 citation statements)
references
References 20 publications
2
62
1
2
Order By: Relevance
“…It is important to note that 46%, 32%, and 23% of patients in the 75-mg, 225-mg, and placebo dose groups, respectively, received bronchodilators; patients using bronchodilators had greater reductions of P. aeruginosa sputum loads and better improvement of lung function. The susceptibility pattern of the isolates did not change from day 0 to day 14 or 28 (303).…”
Section: Aztreonammentioning
confidence: 92%
See 1 more Smart Citation
“…It is important to note that 46%, 32%, and 23% of patients in the 75-mg, 225-mg, and placebo dose groups, respectively, received bronchodilators; patients using bronchodilators had greater reductions of P. aeruginosa sputum loads and better improvement of lung function. The susceptibility pattern of the isolates did not change from day 0 to day 14 or 28 (303).…”
Section: Aztreonammentioning
confidence: 92%
“…The study authors reported changes in P. aeruginosa sputum load and FEV 1 in comparison to values for the corresponding placebo group but not as a change from baseline, so the data summarized in Table 4 have been deduced from ClinicalTrials.gov registration data. The efficacies of two doses of aztreonam were compared in a placebocontrolled, randomized, phase II study (303). Patients were dosed with either 75 mg or 225 mg aztreonam twice daily for 14 days.…”
Section: Aztreonammentioning
confidence: 99%
“…The viscosity of tracheal aspirate samples makes measurements of the volume both inaccurate and nonreproducible; therefore, drug concentrations were measured per gram of sputum instead of per milliliter. To compare the MIC values, expressed in micrograms per milliliter, with the drug concentrations, expressed in micrograms per gram, we adopted the convention commonly used in studies of cystic fibrosis, in which tracheal aspirate samples are weighed and comparisons are conducted under the assumption that 1 g of sputum equals 1 ml (20,21). a GES, Guiana extended-spectrum ␤-lactamase; KPC, Klebsiella pneumoniae carbapenemase; OXA, oxacillin-hydrolyzing extended-spectrum ␤-lactamase; VIM, Verona integron-encoded metallo-␤-lactamase.…”
Section: Control Strainsmentioning
confidence: 99%
“…Nebulized tobramycin has been used for years as an effective anti-Pseudomonal therapy, and many other inhaled antibiotic formulation have been studied (Ryan, Singh et al 2011). Recently, Aztreonam Lysine for Inhalation has been approved in many countries for treatment of chronic CF lung infections, and studies have shown that use of this drug can improve quality of life and pulmonary function of CF patients, while decreasing P. aeruginosa burden and lower exacerbation severity (McCoy, Quittner et al 2008;Retsch-Bogart, Burns et al 2008;Anderson 2010;Bals, Hubert et al 2011). Work continues on other inhaled antibiotics, including aerosolized levofloxacin, fosfomycin/tobramycin, and inhalable dry powers of tobramycin and ciprofloxacin (Anderson 2010;Bals, Hubert et al 2011).…”
Section: Newer Antimicrobial Strategiesmentioning
confidence: 99%